I need to know how to solve this problem

(ab)^{c} = a^{c}b^{c}

((a)^{b})^{c} = a^{bc}

~~~~~~~~~~~

(4y^{3})^{2} = 4^{2}(y^{3})^{2} = **
16y ^{6} **

I need to know how to solve this problem

Tutors, please sign in to answer this question.

^{c} = a^{c}b^{c}

((a)^{b})^{c} = a^{bc}

~~~~~~~~~~~

(4y^{3})^{2} = 4^{2}(y^{3})^{2} = **
16y ^{6} **

For the first step we use (ab)^{n} = a^{n}b^{n}.

For the second step we use (a^{n})^{m} = a^{nm}.

(4y^{3})^{2} = 4^{2}(y^{3})^{2} = 16y^{6}.

Jeffrey G.

Former Med-Student turned Professional Science Tutor

Brooklyn, NY

5.0
(368 ratings)

Amaan M.

Math/Economics Teacher

New York, NY

5.0
(68 ratings)

Dana R.

English/Math SAT PrepTutor with PhD

Lynbrook, NY

4.8
(85 ratings)